Stable mercury concentrations of tropical tuna in the south western Pacific ocean: An 18-year monitoring study. (January 2021) - Médieu, Anaïs; Point, David; Receveur, Aurore; Gauthier, Olivier; Allain, Valérie; Pethybridge, Heidi; Menkes, Christophe E.; Gillikin, David P.; Revill, Andrew T.; Somes, Christopher J.; Collin, Jeremy; Lorrain, Anne
Abstract: Global anthropogenic mercury (Hg) emissions to the atmosphere since industrialization are widely considered to be responsible for a significant increase in surface ocean Hg concentrations. Still unclear is how those inputs are converted into toxic methylmercury (MeHg) then transferred and biomagnified in oceanic food webs. We used a unique long-term and continuous dataset to explore the temporal Hg trend and variability of three tropical tuna species (yellowfin, bigeye, and skipjack) from the southwestern Pacific Ocean between 2001 and 2018 (n = 590). Temporal trends of muscle nitrogen (δ 15 N) and carbon (δ 13 C) stable isotope ratios, amino acid (AA) δ 15 N values and oceanographic variables were also investigated to examine the potential influence of trophic, biogeochemical and physical processes on the temporal variability of tuna Hg concentrations. For the three species, we detected significant inter-annual variability but no significant long-term trend for Hg concentrations. Inter-annual variability was related to the variability in tuna sampled lengths among years and to tuna muscle δ 15 N and δ 13 C values. Complementary AA- and model-estimated phytoplankton δ 15 N values suggested the influence of baseline processes with enhanced tuna Hg concentrations observed when dinitrogen fixers prevail, possibly fuelling baseline Hg methylation and/or MeHg bioavailability at the base of the food web. Our results show that MeHg trends in top predators do not necessary capture the increasing Hg concentrations in surface waters suspected at the global oceanic scale due to the complex and variable processes governing Hg deposition, methylation, bioavailability and biomagnification. This illustrates the need for long-term standardized monitoring programs of marine biota worldwide. Graphical abstract: Image 1 Highlights: Long-term and continuous tuna Hg levels in the SW Pacific Ocean were investigated. Hg levels did not show any significant decadal trend but inter-annual variability. Baseline phytoplankton processes are likely to drive tuna Hg variability. A significant number of bigeye had Hg levels above food safety guideline (1 ppm, ww).